Behavior of Araujiain, a new cysteine phytoprotease, in organic media with low water content - Quiroga, Evelina (2006)
In this paper we studied the effect of different organic solvents (1-octanol, trichloroethylene, ethanol, ethyl acetate, tetrahydrofuran, cyclohexane, propanone, acetonitrile, dichloromethane, chlorobenzene, N,Ndimethylformamide, acetophenone, diethyl ether, methanol, ethylene glycol and toluene) with low and constant water content on substrate preferences, thermostability and stability (caseinolytic activity retention after 4 h) of proteases of Araujia hortorum Fourn. (Asclepiadaceae). The stability of araujiain was high in N,N-dimethylformamide and ethanol at 40ºC, but decreased at higher temperature. Araujiain substrates preferences in buffer Tris-HCl (pH 8), ethylene glycol and N,N-dimethylformamide exhibited different patterns, but the enzyme showed a high preference by glutamine derivative in all cases. According to FTIR spectroscopy studies, araujiain changed its secondary structure and as a consequence, it also changed its substrate preferences. This enzyme showed lower α-helical character and greater β-sheet folding in buffer than in organic media. A larger amount of antiparallel β-sheet residues indicates the formation of tighter intermolecular hydrogen bonds and enzymatic aggregates. These facts could explain the higher esterolytic activities, the greater stability and good hydrolytic potential of araujiain in some organic media such as N,N-dimethylformamide.